Picture Puzzle Book - Usborne; Lucas, Katherine; Russell, Ruth, 1964- (Tulsa, OK : EDC Publishing, 2015)
"This irresistible book contains 25 sumptuously illustrated picture puzzles, each one packed with animals and objects to spot, creatures to count, and lots of delightful details to talk about." --P. [4] of cover.
"First published in 2014 by Usborne Publishing Ltd, London. First published in America in 2015" --P. 31.
Keywords: Picture puzzles -- Juvenile literature; Indoor games